2016
DOI: 10.1136/emermed-2016-205767
|View full text |Cite
|
Sign up to set email alerts
|

Procedural sedation in the emergency department by Dutch emergency physicians: a prospective multicentre observational study of 1711 adults

Abstract: ObjectiveTo describe our experience performing ED procedural sedation in a country where emergency medicine (EM) is a relatively new specialty.MethodsThis is a prospective observational study of adult patients undergoing procedural sedation by emergency physicians (EPs) or EM residents in eight hospitals in the Netherlands. Data were collected on a standardised form, including patient characteristics, sedative and analgesic used, procedural success, adverse events (classified according to World SIVA) and rescu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 23 publications
1
25
2
Order By: Relevance
“…15,[19][20][21][22] In Japan, thiopental, propofol, and midazolam are often used as sedatives for PSA, but thiopental is not commonly used for PSA in North America and Europe, thus it is rarely included in the guidelines for PSA in the ED. 2,4,5 Thiopental has some benefits for PSA such as rapid onset and offset when used as a single dose. However, thiopental also has disadvantages for PSA.…”
Section: Pharmacology Of Psamentioning
confidence: 99%
See 2 more Smart Citations
“…15,[19][20][21][22] In Japan, thiopental, propofol, and midazolam are often used as sedatives for PSA, but thiopental is not commonly used for PSA in North America and Europe, thus it is rarely included in the guidelines for PSA in the ED. 2,4,5 Thiopental has some benefits for PSA such as rapid onset and offset when used as a single dose. However, thiopental also has disadvantages for PSA.…”
Section: Pharmacology Of Psamentioning
confidence: 99%
“…Over the past decade, a number of studies have shown PSA to be safely performed in the ED. [1][2][3][4][5] The availability of ultra-short-acting sedatives and analgesics as well as noninvasive monitoring devices such as capnography have made PSA practice even safer. The availability and common use of sedative and analgesic agents differ depending on region or country.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, sedation often involves greater prevalence of recall as defined by the nature of the targeted clinical condition 13,16,17 . The impact of recall under sedation (RUS) is usually not distressing as patients are expecting some degree of awareness and are not paralyzed, hence, they can signal when becoming aware and/or uncomfortable 13,1822 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, our main study question was whether the P/A index would tend to be different between sedated patients who have recall (as identified by Brice questionnaire 34 – see below) and sedated patients who do not have recall. However, sedation is performed with various drugs and it is known different drugs might have different effect on EEG 35 , on the one hand and different likelihood of recall, on the other hand 16,17,36 . Therefore, despite the pilot nature of this study and its limited sample size and characteristics, we sought ways to evaluate, in a very preliminary manner, whether a possible association between the P/A index and recall might be related to drug type.…”
Section: Introductionmentioning
confidence: 99%